Acute gastric dilatation with infarction and perforation: Report of fatal outcome in patient with anorexia nervosa. Issue 11 (November 1981) - Saul, S H; Dekker, A; Watson, C G
Abstract : This is a report of a 22-year-old woman with treated anorexia nervosa who died of complications of acute gastric dilatation—that is, infarction and perforation with severe and irreversible shock. Binge eating and drinking, precipitated by emotional crises, contributed to her acute gastric dilatation. This complication of anorexia nervosa has been previously reported, but, unlike the others, this case ended fatally. The literature is reviewed.